The Effect of Coconut Shell Liquid Smoke Concentration and Storage Time on The Quality of Fresh Cob Fillet - mudasir mudasir; Ruka Yulia; Irmayanti Irmayanti (Universitas Serambi Mekkah, 2021)
This study aims to determine the effect of the concentration of coconut shell waste liquid smoke on the preservation of tuna, determine the effect of storage time on the preservation of tuna, determine the effect of the interaction between liquid smoke and storage time on the preservation of tuna. The study used a descriptive method with two factors, namely the concentration of coconut shell liquid smoke, namely 1, 2, 3%. The data was taken on the storage time, namely 1 day, 3 days, 5 days. The results showed that the best conditions for preserving fresh cob fillets were from a concentration of 2% liquid smoke and a storage time of 5 days. with the highest water content of 70.64%, pH of 2.23, aroma organoleptic test of 3.65 (like), and texture organoleptic test of 4.20 (like).